Sugar Conversion of Immature Green Rice Syrup under Solid State Fermentation - Chuayjum, Chainarong; Onsaard, Wiriya; Prakitchaiwattana, Chuenjit (Food Agricultural Sciences and Technology, 2020)
Immature green rice contains high content of –oryzanol as well as -aminobutiric acid (GABA) and found that several bioactive active compounds such as phenolic compounds, chlorophyll, ß-carotene, tocopherol as well antioxidant activities were reported. Thus, this research is aimed to add more value of immature green rice as a substrate for Isomaltooligosaccharides (IMOs). The scope is studied a sugar conversion from immature green rice during liquefaction using solid state fermentation (SSF) of Aspergillus oryzae TISTR 3102. The process included, gelatinization of immature green rice starter inoculation as solid state with A. oryzae and under 30 oC for 8 days. The highest syrup volume was obtained after 7 days of fermentation (p≤0.05) with increasing of total soluble solids (oBrix) is (p>0.05). Moreover, reducing sugar found increased and the highest value was observed at the 4th day of fermentation (p≤0.05) and tended to constant through fermentation period. The highest total solid content (%) was found at the 6th day of fermentation (p≤0.05) and tended to decreasing. pH value was decreased from 5.27 ± 0.01 to 4.73 ± 0.01 after 7 days of fermentation (p≤0.05). Ultra-High-Performance liquid Chromatography (UHPLC) was conducted for sugar and isomaltose analysis and the highest amounts of glucose, maltose and isomaltose were observed in 3 and 8 days of fermentation. As monosaccharide was produced by SFF of A. oryzae, it is agreed with increasing of syrup volume, total soluble solid and reducing sugar content and dextrose equivalent.